There is a misprint (which we'll corrrect!), though your solution for (2) is not correct, either.
Algebraically, you can do the following with statement (2):
x^2 > x
(x^2) - x > 0
(x)(x - 1) > 0
A product is positive when you have pos*pos or neg*neg, so
(x)(x - 1) is pos*pos when x > 1.
(x)(x - 1) is neg*neg when x < 0.
The solution is therefore x > 1 or x < 0.You could also test values, either to determine the ranges of values that "work" or to verify the solutions above:
For x = -10, x^2 = 100. 100>-10, so x^2 > x. OK
For x = -1/2, x^2 = 1/4. 1/4 > -1/2, so x^2 > x. OK
For x = neg, x^2 = pos. pos > neg, so x^2 > x. OK
For x = 1/2, x^2 = 1/4. 1/4 < 1/2, so x^2 is not > x. NO
For x = 1, x^2 = 1. 1 = 1, so x^2 is not > x. NO
For x = 2, x^2 = 4. 4 > 2, so x^2 > x. OK
ooisuankim Wrote:The answer I got was: x > 1 (when x > 0) and x < 1 (when x < 0).
Please clarify how is it possible to get x < -1.
Abbout your logic, I'll point out that when you have x < 1 as your solution for the x < 0 case, there's some conflict: 0<x<1 are not negative solutions!